Using Syllabus as Metaphor for Investigating Communicative Risk in Contemporary Risk Communication Research: A Critical Pedagogical Perspective - Minglei Zhang (Journal of Linguistics and Communication Studies, 2023)
This paper explores the potential of utilizing the syllabus as a metaphor for investigating communicative risk and its contribution to contemporary risk communication research. The normalized discourse of “experts vs. laymen” in risk communication produces an asymmetrical relationship when risk information is presented to the public. The syllabus, however, provides a place for risk communication scholars to practice essential functions such as pragmatic and constitutive to the public. The syllabus is not only a practice that navigates relations between the scientists as educators and the public audience as students but also a mediator that affords representation of communicating various visible public risks in the public sphere. The paper argues that recognizing communicative risk and its impact on conceptualizing risk perception through the metaphor of syllabus is critical to reconsider the interdependent relationship between risk and communication and the interdisciplinarity of risk communication research. The paper concludes that the syllabus could become a solution to overcoming the discursive construction of “experts vs. laymen” by providing a forum for inclusive public discussion and empowering the public to feel, reflect, and express how risk plays a role in their everyday lives.